(untitled) (Research, Society and Development, 2021)
Introduction: Congenital syphilis is an infectious disease that has the etiological agent Treponema pallidum. Its transmission is vertical hematogenous, transplacental, of infected pregnant untreated or inadequately treated for its concept. It divides into two periods: early to the second year of life, and after the second year of life, late. Detection during prenatal care is performed by screening the third trimester of pregnancy with preterm labor, as early as in the maternity ward. The detection of Treponema pallidum through non-treponemal test (VDRL), presents little specificity, high sensitivity, low cost and fast negativation in response to the treatment avoiding that the concept is born with sequels. Thus, prenatal care is an important tool in the control of the disease, and it is necessary to improve care quality, since 70% of the mothers in Brazil are prenatal, not all of them are diagnosed or have the appropriate treatment of syphilis. Objective: To establish an epidemiological panorama of the incidence of Congenital Syphilis in the socioeconomic and cultural context in which the School Hospital of the Southern Region of the city of São Paulo is inserted. Patients and Methods: This is an individualized, observational, cross-sectional study carried out by means of a medical records survey of the Hospital Infection Control Service of Hospital Escola da Região Sul in the city of São Paulo. The survey of data referring to the form with questions of interest to the mother and the newborns diagnosed with Congenital Syphilis in the period from 2012 to 2016 was developed. This project was submitted and approved by the Ethics Committee of the Santo Amaro University - SP (Plataforma Brasil - CAAE: 68103317.6.3001.5447). Results: A total of 183 cases of Congenital Syphilis were registered in the Hospital Infection Control Service of the São Paulo School Hospital from 2012 to 2016, and among these, 126 medical records were reinforced. Prenatal performance (p = 0.0060), schooling (p = 0.5107) and schooling (p = 0.8603) did not influence disease screening by showing insignificant statistical data. Success occurred with companion treatment (p = 0.0451), which showed the highest incidence in 2014 (48.1%) and 2016 (58.3) when compared to the others. Conclusion: In the presented scenario, it was verified that although prenatal and maternal treatment were performed, they were inefficient to prevent pregnant women from transmitting the disease. This is probably related to the inefficiency of the treatment of the companions, who although in the year 2014 and 2016 presented a higher incidence of accomplishment, coincided with the increase of notifications in those same years. There were no statistically significant differences in relation to other factores, a fact that causes concern in the field of Public Health.